Beyond antibiotic prescribing rates: first-line antibiotic selection, prescription duration, and associated factors for respiratory encounters in urgent care - Allan M. Seibert; Carly Schenk; Whitney R. Buckel; Payal K. Patel; Nora Fino; Valoree Stanfield; Adam L. Hersh; Eddie Stenehjem (Cambridge University Press, 2023)
Abstract Objective: Assess urgent care (UC) clinician prescribing practices and factors associated with first-line antibiotic selection and recommended duration of therapy for sinusitis, acute otitis media (AOM), and pharyngitis. Design: Retrospective cohort study. Participants: All respiratory UC encounters and clinicians in the Intermountain Health (IH) network, July 1st, 2019-June 30th, 2020. Methods: Descriptive statistics were used to characterize first-line antibiotic selection rates and the duration of antibiotic prescriptions during pharyngitis, sinusitis, and AOM UC encounters. Patient and clinician characteristics were evaluated. System-specific guidelines recommended 5-10 days of penicillin, amoxicillin, or amoxicillin-clavulanate as first-line. Alternative therapies were recommended for penicillin allergy. Generalized estimating equation modeling was used to assess predictors of first-line antibiotic selection, prescription duration, and first-line antibiotic prescriptions for an appropriate duration. Results: Among encounters in which an antibiotic was prescribed, the rate of first-line antibiotic selection was 75%, the recommended duration was 70%, and the rate of first-line antibiotic selection for the recommended duration was 53%. AOM was associated with the highest rate of first-line prescriptions (83%); sinusitis the lowest (69%). Pharyngitis was associated with the highest rate of prescriptions for the recommended duration (91%); AOM the lowest (51%). Penicillin allergy was the strongest predictor of non-first-line selection (OR = 0.02, 95% CI [0.02, 0.02]) and was also associated with extended duration prescriptions (OR = 0.87 [0.80, 0.95]). Conclusions: First-line antibiotic selection and duration for respiratory UC encounters varied by diagnosis and patient characteristics. These areas can serve as a focus for ongoing stewardship efforts.